The attitudes and activities of pastors and faith leaders in Zimbabwe on the use of family planning methods among their members - Moses Alikali (Health for All Nations, 2017)
Background: Faith leaders are important gatekeepers in disseminating reproductive health messages and influencing positive behaviour change within communities. Faith leaders are seen as the most powerful, visible, and reachable form of authority, even trusted more than governments or non-profit organizations. In addition to providing counsel and advice aimed at enhancing health and wellbeing of the worshippers, faith leaders also play an important role in advocating and influencing what is taught in schools and what services are provided in healthcare facilities. Because of this influence, faith leaders often have an unparalleled opportunity-indeed, a moral obligation-to prioritize conversations about family planning, advocating, and closing the contraception gap.The overall objective of this study was to ascertain the attitude and activities of pastors and faith leaders in Zimbabwe on the use of family planning methods among their members. The result revealed that some faith leaders believed that spreading information about family planning education was the responsibility of the government and tended to avoid such responsibility. However, through training on family planning advocacy, much can be achieved. Methods: Qualitative study methods were used to better understand the attitude and activities of pastors and faith leaders in Zimbabwe on the use of family planning methods among their members. The participants of this survey were drawn from 8 of 10 provinces in Zimbabwe, which include: Bulawayo, Harare, Manicaland, Mashonaland Central, Mashonaland East, Mashonaland West, Masvingo, and Matabeleland North.Paper-based questionnaires were answered by 24 pastors and 26 faith leaders in Zimbabwe (Table 1) through personal face-to-face meetings, while interviews were conducted with a select few pastors and faith leaders. The samples were drawn from randomly selected churches in Zimbabwe. Data was analysed using Epi info 7 and Microsoft Excel. Results: Generally, the pastors and faith leaders understood the benefits of longer birth intervals for the health of their members and their children, and the need for them to be involved in family planning awareness. However, both seemed slow to incorporate family planning into their programs. The faith leaders indicated an interest in being a part of various forms of campaigns to promote family planning if they could be equipped with correct information on family planning. Many strongly believed family planning to be of great importance to them and their families in situations where their financial incomes were low, and that family planning could reduce the rate of abortion. A majority agreed family planning was in agreement with their religious beliefs. Some felt their members had basic information on family planning methods, but only 44 percent of the faith leaders actually counselled their members on family planning methods from time to time. Although many would like to be part of those who create awareness in their various places of worship, only 28 percent of them had the right information on family planning through training. Conclusion: One major factor for the limited involvement of faith leaders in family planning awareness is their lack of correct information on family planning. The gap can be narrowed by organizing family planning advocacy training workshops. Networks such as Africa Christian Health Association Platform (ACHAP), the Islamic Medical Association of Zimbabwe (IMAZ), Zimbabwe Association of Church-Related Hospitals (ZACH), and Zimbabwe Council of Churches (ZCC) can also be leveraged to disseminate and accelerate the spread of family planning information.